Exploring Manually Curated Annotations of Intrinsically Disordered Proteins with DisProt. Issue 1 (5th October 2020) - Quaglia, Federica; Hatos, András; Piovesan, Damiano; Tosatto, Silvio C. E.
Abstract: DisProt is the major repository of manually curated data for intrinsically disordered proteins collected from the literature. Although lacking a stable tertiary structure under physiological conditions, intrinsically disordered proteins carry out a plethora of biological functions, some of them directly arising from their flexible nature. A growing number of scientific studies have been published during the last few decades in an effort to shed light on their unstructured state, their binding modes, and their functions. DisProt makes use of a team of expert biocurators to provide up‐to‐date annotations of intrinsically disordered proteins from the literature, making them available to the scientific community. Here we present a comprehensive description on how to use DisProt in different contexts and provide a detailed explanation of how to explore and interpret manually curated annotations of intrinsically disordered proteins. We describe how to search DisProt annotations, using both the web interface and the API for programmatic access. Finally, we explain how to visualize and interpret a DisProt entry, p53, a widely studied protein characterized by the presence of unstructured N‐terminal and C‐terminal regions. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Performing a search in DisProt Support Protocol 1 : Downloading options Support Protocol 2 : Programmatic access with DisProt REST API Basic Protocol 2 : Visualizing and interpreting DisProt entries: the p53 use case Basic Protocol 3 : Providing feedback and submitting new intrinsic disorder−related data